Ecosystems-based adaptation in the forest and agriculture interface: Operationalizing action in Mondulkiri and Koh Kong - International Institute of Rural Reconstruction; Cambodian Center for Study and Development in Agriculture (2020)
A range of interventions within the scope of ecosystems-based adaptation (EbA) are being deployed to address the continuing degradation of forest cover, within protected areas and biodiversity conservation corridors in Cambodia. Ecosystem adaptation has involved the use of ecosystem services as part of the overall adaptation strategy. Forest landscape restoration (FLR) is an important dimension in the ADB supported BCCP efforts. This involves mosaic restoration featuring climate-smart agriculture agroforestry, and related conservation work in Koh Kong and Mondulkiri provinces. Ecosystem-based approaches are considered cost-effective due to the multiple environmental, economic, and social benefits they provide.